SISTEM PENGOLAHAN DATA MEDIA MONITORING BERBASIS WEB PADA PT. INDOPRIMA MEDIA PRATAMA - Destiana, Henny; Anshori, Ahmad Hisyam (Jurnal Pilar Nusa Mandiri, 2013)
This study discusses data processing in PT. Indoprima Media Pratama (Indopres), which is a media consulting firm that serving clients to provide information in the form of clippings based media list, keyword and press release in accordance with the client's request. Currently, a clipping news article is sent by email, which often has errors due to large file size when uploaded to the email. Through this study, the authors analyze and propose the design of a web-based data processing system that is featured with client registration system and online payment confirmation. A target of this system is to minimize error and to facilitate the coordination of PT Indoprima Media Pratama (Indopres) with its client